PHYSICOCHEMICAL AND MICROBIOLOGICAL EVALUATION OF THE EXTRACTION OF OCA FLOUR BY THE OPEN TACHO METHOD - Caicedo, Dayana (2021)
Flours have been fundamental for the elaboration of products with greater nutritional properties, which is why a physicochemical and microbiological evaluation of the extraction of goose flour by the open container method was carried out in order to increase its consumption. Fresh geese were used and in good conditions which used a sweetening time of 15 days exposed to the sun, then they proceeded to wash, disinfect and cut into flakes with a diameter of 2mm to subject them in a solution of citric acid at 0.1 % normal. Subsequently, the pre-cooking of the flakes was carried out in an open pan, a method that consists of applying heat at 91°C for 20 minutes with a pressure of 10.44 PSI. Finally, the goose flakes are taken to a drying process for 20 hours for their respective grinding and sieving until the flour is extracted to which the different analyzes will be made. The results presented by the goose flour were a pH of 7.43%, humidity 9.32%, ash 4.23%, protein 6.28%, fiber 2.98%, fat 0.83%, carbohydrates 77, 25%, which means that it complies with the physicochemical requirements established in the NTE INEN 616 standard, as well as its microbiological analysis since the count of cfu / g of coliforms, molds and yeasts was lower than the maximum permitted limits.